Anatomia óssea da cintura pelvina, estilopódio e zeugopódio e muscular da cintura pelvina e estilopódio de caiman crocodilus - Romão, Mariluce Ferreira (2015)
CHAPTER II: The objective was to identify the pelvic girdle, stylopod and zeugopod bone anatomy of the Caiman crocodilus, assuming that such information contributes to improve the knowledge about the locomotor system of these animals. Four samples of the C. crocodilus, males, measuring an average length of 1,50m, adults belonging to the didactic collection of the Laboratory of Education and Research of Wild Animals (Laboratório de Ensino e Pesquisa em Animais Silvestres - LAPAS), from the Federal University of Uberlândia (Universidade Federal de Uberlândia), already set in 10% formalin, were used. The dissection was performed, initiating with a longitudinal incision, along the ventral median line of the trunk, folding the skin laterally, from the cervical region to the caudal thoracolumbar level, allowing the removal of the viscera en bloc. In the following, the pelvic girdle, the stylopod and zeugopod were disarticulated from the trunk, going through a maceration process with boiling and submersion in hydrogen peroxide at 20 volumes, until satisfactory clarification, for the identification and description of the bone features. A pelvic girdle was identified with three bony constituents: ilium, ischium and pubis. The ilium, with dorsolateral localization, is constituted by a wing and a body. The ischium, localized ventrolaterally and caudal, is constituted by a body, a ramus and a slate with a larger caudal extension. The pubis, with ventral and cranial placement, is constituted by a body, a ramus and a slate with larger cranial extension. The stylopod consists of the femur, with emphasis to the fourth trochanter most prominent in fossil reptiles. The zeugopod consists of the tibia with larger diameter, located medially, and the fibula, with smaller diameter, located laterally. The C. crocodilus presents larger similarity with living archosaurs, in view of the locomotor behavior that defines and explains, in large part, the adaptations to the evolutionary process, as well as the influence of habits from terrestrial ancestrals, and currently, the semiaquatic Crocodylia. CHAPTER III: The objective was to study the muscular anatomy of the pelvic girdle and stylopod of the Caiman crocodilus, augmented of kinesiological correlations, and homology in some groups of tetrapods, under the assumption that such information can contribute to improve the knowledge about the locomotor system of these animals. Four samples of the C. crocodilus, set in 10% formalin, males, measuring an average length of 1,50m, adults belonging to the didactic collection of the Laboratory of Education and Research of Wild Animals (Laboratório de Ensino e Pesquisa em Animais Silvestres), from the Federal University of Uberlândia (Universidade Federal de Uberlândia), were used. The dissection was performed, initiating with a longitudinal incision, along the ventral median line of the trunk, folding the skin laterally, until the tail. Next, the muscles of the pelvic girdle and stylopod of the C. crocodilus were individualized and identified, with verification of the respective muscular origins and insertions. In a lateral and superficial view, there was the identification of the internal puboischiofemoral muscle 2, iliotibial group (heads 1, 2 and 3), and iliofibular muscle. In a deep lateral view (Table 2) the external femorotibial and iliofemoral muscles were identified. In a superficial and medial view, there was the identification of the ambiens group (head 1 and 2), internal puboischiofemoral muscle 1, external puboischiofemoral group (heads 1, 2 and 3), femoral adductor muscle 1, puboischiotibial, internal tibial flexor (heads 1 and 2), external tibial flexor, and caudofemoral group (long and short). In a deep medial view, the internal puboischiofemoral muscle 1, femoral adductor 2, internal tibial flexor 3, and ischiotrochanteric muscles were identified. The muscular anatomy of the pelvic girdle and stylopod of the Caiman crocodilus confirms the morphological diversity, in terms of greater responsibility directed to functional activities, for presenting differences, including with the living Crocodylia. The external pubioischiofemoral group was considered the most similar in the comparisons, and the internal tibial flexor group, the most diverse. Functional adaptations due to evolution happen, with tendency to minimize and redirection functions.